Human Dedifferentiated Adipocytes Show Similar Properties to Bone Marrow‐Derived Mesenchymal Stem Cells123. (9th April 2012) - Poloni, Antonella; Maurizi, Giulia; Leoni, Pietro; Serrani, Federica; Mancini, Stefania; Frontini, Andrea; Zingaretti, M. Cristina; Siquini, Walter; Sarzani, Riccardo; Cinti, Saverio
Abstract: Mature adipocytes are generally considered terminally differentiated because they have lost their proliferative abilities. Here, we studied the gene expression and functional properties of mature adipocytes isolated from human omental and subcutaneous fat tissues. We also focused on dedifferentiated adipocytes in culture and their morphologies and functional changes with respect to mature adipocytes, stromal‐vascular fraction (SVF)‐derived mesenchymal stem cells (MSCs) and bone marrow (BM)‐derived MSCs. Isolated mature adipocytes expressed stem cell and reprogramming genes. They replicated in culture after assuming a fibroblast‐like shape and expanded similarly to SVF‐ and BM‐derived MSCs. During the dedifferentiation process, mature adipocytes lost their lineage gene expression profile, assumed the typical mesenchymal morphology and immunophenotype, expressed stem cell genes and differentiated into multilineage cells. Moreover, during the dedifferentiation process, we showed changes in the epigenetic status of mature adipocytes, which led dedifferentiated adipocytes to display a similar DNA methylation condition to BM‐derived MSCs. Like SVF‐ and BM‐derived MSCs, dedifferentiated adipocytes were able to inhibit the proliferation of stimulated lymphocytes in coculture while mature adipocytes stimulated their growth. Furthermore, dedifferentiated adipocytes maintained the survival and complete differentiation characteristic of hematopoietic stem cells. This is the first study that in addition to characterizing isolated and dedifferentiated adipocytes also reports on the immunoregulatory and hematopoietic supporting functions of these cells. This structural and functional characterization might have clinical applications of both mature and dedifferentiated adipocytes in such fields, as regenerative medicine. STEM CELLS 2012;30:965–974